An adaptive coordinated optimal control method for parallel bidirectional power converters in AC/DC hybrid microgrid. (March 2021) - Li, Peng; Guo, Tianyu; Li, Yuwei; Han, Xiaoqing; Wang, Peng; Li, Xinming; Wang, Zixuan
Highlight: The economically optimal distribution scheme of BPCs is calculated. A non-linear coordinated control method for BPCs is proposed. A secondary voltage-regulated controller for BPCs is designed to control dc voltage. Abstract: Parallel bidirectional power converters (BPCs) play an important role in achieving mutual support between the two grids and in improving the power quality. One of the difficulties of the study is how to coordinated control BPCs to simultaneously realize the dual goals of economically distribute transmission power among BPCs and the high dynamic quality. In view of this, this paper proposes an adaptive coordinated optimal control method for the parallel BPCs. First, taking the minimization of the sum of the power losses of BPCs as the objective, the economically optimal distribution scheme for power transmission among parallel BPCs is calculated. Second, a primary voltage-regulated controller is designed, outer loop of the primary voltage-regulated controller can distribute the dynamic transmission power among BPCs according to the power margin of each BPC, to avoid overloading BPCs, and inner loop of the primary voltage-regulated controller can realize the decoupling of the output variable and the interference variable, to improve the dynamic voltage quality. Third, a secondary voltage-regulated controller is designed, it can make the dc bus voltage restore to the rated value quickly after power disturbance occurs, and ensure the economically optimal distribution of the transmission power among BPCs after the system reaches the steady state. Finally, the stability of the proposed control method is illustrated and conclusions are verified.